Gamaespectrometria terrestre aplicada as rochas vulcânicas da província magmática do Paraná - Kanashiro, Daniel Kenzi [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The Magmatic Province of Parana (PMP), scope of this work, was one of the biggest continental volcanic floods during the lower cretaceous, covering areas around 2Mkm². In Brazil, this province is composed by three types of volcanic rocks. The first one, majority in the province, is composed by tholeiitic basalt. The second type, with subordinate volumes in the province is composed by andesitic rocks with tholeiitic affinity. The last type and the least common is composed by acidic rocks (rhyodacite-rhyolite) and are classified into two groups: The afitic rocks of Palmas type (ATP) and the porphyritic rocks of Chapecó type (ATC). Although the extensive literature about the lithotypes of PMP, there's still many problems about the understanding of the stratigraphic stacking and the evolutive relations between the basic, intermediate and acidic types of the province. Therefore, the main objective of this work consists in the use of in-situ gamma spectrometry data to find out the potential of this method in the differentiation of the main volcanic rock types of PMP. For this, an association of this gamma spectrometric data with chemical analysis and petrography will be compared to identify patterns that could be used in the future to facilitate the identification and mapping of these volcanic rocks in field work

A Província Magmática do Paraná (PMP), objeto de estudo deste trabalho, foi um dos maiores vulcanismos continentais decorrente do cretáceo inferior, cobrindo áreas da ordem de 2 Mkm2. No Brasil, essa província é composta por três tipos de rochas vulcânicas. O primeiro tipo, que predomina na PMP, é composto por basaltos de origem toleítica. O segundo tipo ocorre em volumes subordinados na província e é composto por rochas de natureza intermediária, representados por andesitos com afinidade toleítica. O terceiro tipo, que é o menos abundante é composto por rochas de natureza ácida (riodacitos-riolitos) e são classificadas em dois grupos principais: As rochas afíticas do tipo Palmas (ATP) e as rochas porfiríticas do tipo Chapecó (ATC). Apesar da extensa literatura acerca dos litótipos da PMP, ainda há diversos aspectos problemáticos acerca do empilhamento estratigráfico e relação evolutiva entre os termos básicos, intermediários e ácidos da província. Assim, o principal objetivo deste trabalho é utilizar dados gamaespectrométricos obtidos em campo com o intuito de averiguar o potencial desse método na diferenciação dos principais tipos de rochas vulcânicas que constituem a PMP. Para isso, será realizada a associação desses dados gamaespectrométricos com dados de campo, petrografia e análise química, a fim de identificar padrões que possam ser usados futuramente para facilitar na identificação e mapeamento dos litótipos da PMP em campo
Keywords: Rochas igneas; Espectrometria de raio gama; Petrologia; Parana